THE PROFILE OF STUDENT'S CONCEPT MASTERY AND ENVIRONTMENTAL AWARENESS IN LEARNING GLOBAL WARMING - Rizal Maulana Fikri, - (2020)
In learning science, one of the most consideration and indicators of the success of the learning is Students 'concept mastery. Students' concept mastery is one of the most essential elements in learning science. Comprehending the concept is one the most crucial aspects in learning. Activities in learning cannot be excluded from concept mastery. The concept mastery can be elaborated with the application of the knowledge such as environmental awareness. Environmental awareness is one of brief visualization of the application of the study learned. However, the goal of this research is to analyze the profile of students' concept mastery and students' environmental awareness in learning global warming topic. In order to answer the research problem, there were 428 students of junior high school involved in this research. Students' concept mastery was analyzed by using 30 number of test items which consist of six level of cognitive domains. Meanwhile students' environmental awareness examined by using questionnaire that distributed virtually using online platform. Based on the result, the students' concept mastery shown the various result based on the cognitive domain level and subtopic of global warming while students' environmental awareness indicated that the students' have different result based on part of environmental awareness. Keywords: students' concept mastery, students' environmental awareness, and global warming topic